2020
DOI: 10.13106/jafeb.2020.vol7.no6.351
|View full text |Cite
|
Sign up to set email alerts
|

Board Gender Diversity and Corporate Sustainability Performance: Mediating Role of Enterprise Risk Management

Abstract: The objective of this paper is to explore how board gender diversity affects corporate sustainability performance. Therefore, this paper examines the direct association between board gender diversity with corporate sustainability performance and the mediation effect of enterprise risk management (ERM) on this association. The study employed a cross-sectional survey method. Data were collected from annual reports, websites, and through the questionnaires that were distributed to Chief Financial Officers (CFOs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…According to agency theory, the more diversity on the board, the better monitoring and management of the corporation's activities (Hassan and Marimuthu, 2016;Madhani, 2017). According to the resource dependency theory, diverse members bring more resources in terms of skills, expertise, advice, and counselling as well as access to the external market (Enache and Garcia-Meca, 2019;Fakir and Jusoh, 2020). Research showed that diversity in terms of gender, nationality, age, and higher education, improves corporate decision-making quality, especially as related to environmental and social activities, which leads to improving sustainability performance (Chams and Garcia-Blandon, 2019;Rao and Tilt, 2016b).…”
Section: Board Diversitymentioning
confidence: 99%
“…According to agency theory, the more diversity on the board, the better monitoring and management of the corporation's activities (Hassan and Marimuthu, 2016;Madhani, 2017). According to the resource dependency theory, diverse members bring more resources in terms of skills, expertise, advice, and counselling as well as access to the external market (Enache and Garcia-Meca, 2019;Fakir and Jusoh, 2020). Research showed that diversity in terms of gender, nationality, age, and higher education, improves corporate decision-making quality, especially as related to environmental and social activities, which leads to improving sustainability performance (Chams and Garcia-Blandon, 2019;Rao and Tilt, 2016b).…”
Section: Board Diversitymentioning
confidence: 99%
“…There is a significant effect on gender and consumption (Roberts, 1998). There is no support for the direct association between board gender diversity and sustainability performance (Fakir and Jusoh, 2020).…”
Section: Research -Conceptual Frameworkmentioning
confidence: 87%
“…Tolerance for risk and failure is one of the main aspects conducive to entrepreneurship (Alpkan et al, 2010). When top leaders provide this tolerance, it means that they give trust, and in time, intrapreneurs are motivated to carry out their initiatives (Fakir & Jusoh, 2020). They know the potential for failure exists, but at the same time, they can hope that their superior will fairly see the consequences.…”
Section: Tolerance With the Riskmentioning
confidence: 99%